Problems in Writing Passive Voice: A Case Study in the EFL Classes - Jannah, Alda Raudatul; Wilian, Sudirman; Zamzam, Ahmad; Arafiq, Arafiq; Arfah, Hajriana (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study addresses EFL students' challenges at a state university in Mataram, Indonesia, in constructing passive voices in the present and past tense. This study was focused on verb tense changes, subject-verb agreement, pronoun usage, and appropriate use of "by" in passive voice constructions. It also aims to explore the causes of these issues and offers insights into potential solutions. With a descriptive qualitative approach, the data were collected using a set of written grammatical tests of passive voices and open interviews. The adopted validated test was completed by thirty students as the participants of this study. The data were analyzed descriptively using an in-depth reading analysis method on the test results and participant responses. The results reveal a need for fundamental grammatical knowledge, limited exposure to passive voice, inadequate practice opportunities, and unclear explanations as contributing factors to the challenges. Language transfer from native languages and a lack of feedback compound the problem. To address these issues, the study recommends basic tense understanding, increased practice, targeted feedback, and exposure to authentic materials to enhance students' proficiency in constructing accurate passive voice sentences.